Exploring the relationship between emotional intelligence and communication skills in nurses: a cross-sectional study - Farid Ghrayeb; Kefah Zaben; Rabia H. Haddad; Nahid Ghrayeb; Mohammad Barhoush; Nashat Zuraikat; Ashraf J. Abuejheisheh (BMC Nursing)
Abstract Aim Patients’ outcomes could be improved by using emotional intelligence (EI) in communication. Many of the behavioral skills of nurses are shaped by their EI. This study aims to explore the relationship between the communication skills of nurses working in hospitals and their EI, emphasizing the importance of communication abilities. Method This cross-sectional study included 350 nurses as a convenience sampling technique working in four government and private hospitals in the southern West Bank of Palestine. The questionnaire consisted of three sections: sociodemographic, EI Goleman’s questionnaire, and communication skills questionnaire. Participants completed a communication skills questionnaire developed by the researcher, along with Goleman’s EI Scale. The validity and reliability of the tools were assessed throughout the study. Data analysis was conducted using descriptive statistics, analysis of variance, and Pearson’s correlation test in SPSS v27. Results The self-awareness dimension achieved the highest score of 25.50, whereas self-management recorded the lowest at 19.69, resulting in an estimated average EI score of 87.22. In terms of communication instruments, a total possible score ranges from 28 to 140, with higher mean scores indicating high EI. The overall average score for communication skills was 90.23. A significant correlation. For EI, a total possible score ranging from 28 to 140, with higher mean scores indicating high EI. was observed between the total EI score and the overall communication skills score (r = 0.542, p < 0.01), and all four EI dimensions were strongly correlated with the total communication skills score. Conclusion As EI and its dimensions positively influence nurses’ communication skills, hospital managers can enhance EI by organizing training sessions, promoting communication skills, and establishing a foundation for continuous improvement in hospital services. The in-service training, including monthly meetings and conferences, would benefit nurses by engaging them with EI. Using artificial intelligence could engage nurses in training sessions. Clinical trial number Not applicable.